2020
DOI: 10.1155/2020/6141847
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Inflammatory, and Analgesic Activities of Aqueous Extract of Diploknema butyracea (Roxb.) H.J. Lam Bark

Abstract: Diploknema butyracea (Roxb.) H.J. Lam is a multipurpose tree used by the Nepalese indigenous people for medicinal purposes such as rheumatism, asthma, and ulcer and other purposes such as cooking and lighting. However, there is no scientific evidence for the medicinal uses of this plant. The present study aimed to explore the phytochemical constituents, estimate the total phenolic content, evaluate antioxidant activity, and investigate the in vivo anti-inflammatory and analgesic activities of aqueous extract o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
4
6
0
Order By: Relevance
“…The DPPH radical absorbs UV radiations at 517 nm. The radical scavenging activity was determined by monitoring the decrease in absorbance [ 22 , 29 ]. Among three individual parts, our investigation flaunted that D. butyracea methanolic root bark extract exhibited the highest capacity to reduce the DPPH free radical (90.52 ± 0.13%) even at the concentration of 200 µ g/ml and the lowest scavenging capacity was exhibited by hexane pericarp extract (18.18 ± 0.2% at 1000 µ g/ml).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DPPH radical absorbs UV radiations at 517 nm. The radical scavenging activity was determined by monitoring the decrease in absorbance [ 22 , 29 ]. Among three individual parts, our investigation flaunted that D. butyracea methanolic root bark extract exhibited the highest capacity to reduce the DPPH free radical (90.52 ± 0.13%) even at the concentration of 200 µ g/ml and the lowest scavenging capacity was exhibited by hexane pericarp extract (18.18 ± 0.2% at 1000 µ g/ml).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the IC 50 value of methanolic root bark (6.1 µ g/ml) was reported to be almost similar to that of standard ascorbic acid (5.15 µ g/ml). The IC 50 value of the D. butyracea aqueous stem bark was determined to be 8.43 µ g/ml in previous research [ 22 ]. In a former study, IC 50 of the methanolic pericarp (104 µ g/ml) [ 20 ] was found almost similar to this study (111.3 µ g/ml).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening. e hydroethanolic extract of S. pinnata leaves was tested for potential chemical constituents through preliminary phytochemical screening using standard methods [19,20].…”
Section: Phytochemicalmentioning
confidence: 99%
“…The species is also planted on margins of agricultural lands for fodder and to restore degraded lands or wastelands (Tewari et al, 2015). Chiuri has antioxidant, analgesic, and anti-inflammatory potential supporting its traditional medicinal uses (Chhetri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%